Geoscience Education in Ghana and Sustainable Development - Asiedu, D.K. (University of Ghana, 2018)
Geoscience is the study of the Earth. It involves the study of the materials of which the Earth is made up of, the structure of these materials, the processes acting upon them, and the organisms that have inhabited the Earth. It also includes the study of how Earth’s materials, structures, processes and organisms have changed over time. Geoscientists study the Earth to understand the history of our planet. This is very important because the better we can understand Earth’s history the better we can foresee how events and processes of the past might influence the future. Geoscience is fundamental to us as humans because it deals with Earth, the planet we live on, and its resources. Earth materials such as sand and gravel are used to make concrete to build, for example, houses and roads. Rocks are made up of aggregates of minerals and mineral products surround us in our ordinary daily life; minerals can be found in mobile phones, personal computers, cables, cars, makeup products, paints, papers, batteries, etc. Basic knowledge of Geoscience is essential to meeting the environmental challenges and natural resource limitations of the 21st century. Understanding the causes and potential societal consequences of natural Earth processes (e.g., earthquakes, floods, landslides, tsunamis, volcanic eruptions, weather, and global climate change) and the production, availability, and potential depletion of natural resources (e.g., water, soil, mineral, and energy) are of particular importance because they impact our economy, our security, and the safety and sustainability of our environment. Geoscience has an important role to play in helping to achieve the SDGs, through the efforts and contributions of Geoscience workforce which includes educators, researchers, industry professionals, students, public servants and policymakers, to ensure sustainable and equitable foundations for future global development. Their knowledge of the Earth’s structure, the materials it is made of, and the processes acting upon it can be used to inform many important areas of sustainable development such as access to clean water and safe sanitation, food security and agrogeology, disaster risk reduction, energy supply and management, improved infrastructure and access to basic services, and environmental and biodiversity management and conservation. The critical needs of the Ghanaian society include the following: (i) ensuring reliable energy supplies, (ii) providing sufficient supplies of water (ii) managing waste to maintain a healthy environment, and (iv) mitigating risk and building resilience from natural and human-made hazards. Given the importance of Geoscience in our everyday lives, it is vital to, on regular basis, inform and educate the general public on Geoscience issues that are related to the critical needs of the Ghanaian society. However, the level of Geoscience literacy in the country is very low. To address this issue there is the need to train more Earth scientists. Despite this glaring need for Geoscience literacy the science curricula of our elementary and secondary schools do not cover as many topics in Geoscience as they do in other science disciplines such as chemistry, physics or biology. Moreover, there is a shortage of teachers with an academic degree in Geoscience compared to other science disciplines. Conversely, it is critical that students understand how the Earth works as a system and how humans interact with the Earth. It is important that the study of Geoscience be made an integral component of science education in schools at all levels, from primary through to senior high school, and that highly qualified Earth science teachers provide the instruction. Earth science is an integrated science, bringing together chemistry, physics, and biology as they apply to the workings of the Earth. The applied and visual nature of Earth science helps learners to see the connections and relevance of science to their lives and their communities. Engaging students in learning about the Earth supports the development of problem solving and critical thinking skills and highlights the importance of science, technology, engineering, and mathematics (STEM) careers to society. Given the critical need for a skilled Geoscience workforce and more robust Geoscience education in Ghana, the Government of Ghana, through its relevant agencies, should promote the following: • Provide incentives for both public and private universities running science programmes in education to include a Geoscience programme. • Provide incentives for both public and private universities to introduce compulsory general education courses in the Geosciences. • Introduce Geoscience courses in the science curriculum of the colleges of education. • Review the science curricula in our primary and secondary schools to include a substantial component of Earth science. • Provide greater support for scholarships, grants, and fellowships for students majoring in Geoscience at undergraduate and graduate levels. • Actively engage the Geoscience workforce in the achievement of the SDGs. • Empower and support the Geoscience workforce, led by the Ghana Institution of Geoscientists, to undertake regular public outreach and informal geoscience education in the news media (print, electronic, TV, social media), and at geotourist centres.
Keywords: Geoscience Education; Sustainable Development; Ghana